Mass spectrometry imaging of freeze‐dried membrane phospholipids of dividing Tetrahymena pyriformis. (14th June 2012) - Lanekoff, Ingela; Phan, Nhu TN.; Van Bell, Craig T.; Winograd, Nicholas; Sjövall, Peter; Ewing, Andrew G.
<x xml:space="preserve">Abstract</x> Time of Flight secondary ion mass spectrometry (TOF‐SIMS) has been used to explore the distribution of phospholipids in the plasma membrane of Tetrahymena pyriformis during cell division. The dividing cells were freeze‐dried prior to analysis followed by line scan and region of interest analysis at various stages of cell division. The results showed no signs of phospholipid domain formation at the junction between the dividing cells. Instead the results showed that the sample preparation technique had a great impact on one of the examined phospholipids, namely phosphatidylcholine (PC). Phosphatidylcholine and 2‐aminoethylphosphonolipid (2‐AEP) have therefore been evaluated in Tetrahymena cells that have been subjected to different sample preparation techniques: freeze drying ex situ, freeze fracture, and freeze fracture with partial or total freeze drying in situ. The result suggests that freeze drying ex situ causes the celia to collapse and cover the plasma membrane. Copyright © 2012 John Wiley & Sons, Ltd.